Can nutrition be promoted through agriculture-led food price policies? A systematic review. Issue 6 (25th June 2013) - Dangour, Alan D; Hawkesworth, Sophie; Shankar, Bhavani; Watson, Louise; Srinivasan, C S; Morgan, Emily H; Haddad, Lawrence; Waage, Jeff
Abstract : Objective: To systematically review the available evidence on whether national or international agricultural policies that directly affect the price of food influence the prevalence rates of undernutrition or nutrition-related chronic disease in children and adults. Design: Systematic review. Setting: Global. Search strategy: We systematically searched five databases for published literature (MEDLINE, EconLit, Agricola, AgEcon Search, Scopus) and systematically browsed other databases and relevant organisational websites for unpublished literature. Reference lists of included publications were hand-searched for additional relevant studies. We included studies that evaluated or simulated the effects of national or international food-price-related agricultural policies on nutrition outcomes reporting data collected after 1990 and published in English. Primary and secondary outcomes: Prevalence rates of undernutrition (measured with anthropometry or clinical deficiencies) and overnutrition (obesity and nutrition-related chronic diseases including cancer, heart disease and diabetes). Results: We identified a total of four relevant reports; two ex post evaluations and two ex ante simulations. A study from India reported on the undernutrition rates in children, and the other three studies from Egypt, the Netherlands and the USA reported on the nutrition-related chronic disease outcomes in adults. Two of the studies assessed the impact of policies that subsidised the price of agricultural outputs and two focused on public food distribution policies. The limited evidence base provided some support for the notion that agricultural policies that change the prices of foods at a national level can have an effect on population-level nutrition and health outcomes. Conclusions: A systematic review of the available literature suggests that there is a paucity of robust direct evidence on the impact of agricultural price policies on nutrition and health.